Playing the Rebab: Unmasking Transcultural Practices of Jazz and Improvisation - Yeoh, Pei Ann (Critical Studies in Improvisation / Études critiques en improvisation)

(untitled) (University of Guelph College of Arts, 2025)
This is a reflective account of a transcultural practice through improvisation, stemming from a background in jazz. Musical intersections emerge when aspects of culture and heritage are examined against improvisatory codes and traditions. As a result, a transcultural encounter is developed through the author's search for new modes of expression beyond the construct of a jazz vocabulary. Drawing on traditional Malay practice of the rebab, the paper will examine the social and spiritual rituals that prescribe and parallel those in the jazz tradition, interacting with traditional values while innovating its practices. Through this, a double-consciousness is shaped to question which culture does one belong to when improvising and what responsibilities might we hold up to our heritage and identity.